2017
DOI: 10.18632/oncotarget.14497
|View full text |Cite
|
Sign up to set email alerts
|

Identifying genetic hypomethylation and upregulation of toll-like receptors in Kawasaki disease

Abstract: Kawasaki disease (KD) is an acute febrile systemic vasculitis that occurs in children and is characterized by elevated levels of proinflammatory cytokines. Toll-like receptors (TLRs) serve as the sensor arm of the innate immune system and induce proinflammatory cytokine expressions.We recruited a total of 18 paired KD patients, before intravenous immunoglobulin (IVIG) and at least 3 weeks after IVIG treatment, 18 healthy controls, and 18 febrile controls. For TLR genes and their cytosine-phosphate-guanine (CpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 34 publications
5
75
0
Order By: Relevance
“…While the exact etiology of KD remains uncertain, we have reported that KD stimulates the extraordinary upregulation of TLR1, 2, 4, 5, 6, and 9, which correlates with bacteria-related pathogen-associated molecular patterns, except for the activation of TLR3 and 7, which relates to double-stranded RNA and single-stranded viral RNA in the acute stage of KD. [8]. This study’s results support the idea that KD induces a bacterium-like inflammatory disease.…”
Section: Kawasaki Disease: the Most Common Acute Coronary Vasculitsupporting
confidence: 84%
“…While the exact etiology of KD remains uncertain, we have reported that KD stimulates the extraordinary upregulation of TLR1, 2, 4, 5, 6, and 9, which correlates with bacteria-related pathogen-associated molecular patterns, except for the activation of TLR3 and 7, which relates to double-stranded RNA and single-stranded viral RNA in the acute stage of KD. [8]. This study’s results support the idea that KD induces a bacterium-like inflammatory disease.…”
Section: Kawasaki Disease: the Most Common Acute Coronary Vasculitsupporting
confidence: 84%
“…Regarding the implication of PRRs, Huang et al (100) reported that the CpG sites of TLR genes were reversibly hypomethylated in the peripheral whole blood cells of acute KD patients, resulting in upregulated expression of TLRs. This transient epigenetic change supposedly potentiates the TLR-dependent innate immune response.…”
Section: Other Insight To Pamps/mamps Hypothesis In Kdmentioning
confidence: 99%
“…We have previously reported that IVIG administration significantly affects methylation pattern alterations in KD patients [17][18][19]. In short, DNA methylation can affect an inactive gene through DNA methyltransferases [20].…”
Section: Introductionmentioning
confidence: 99%